(3GdJMdjd GdGMUGFj hJWHjbGJg aj OQGSGJ GdNOeI GdGLJeGYjIs - (3GdSjO YHO GdMejO(B, (3YWjIs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2001)
(3aj gPG GdcJGH GdYjfGJ (B2- (3GNJHGQGJ eYfhjI GdEQJHGW hGdGfMOGQ (B3- (3GdGMJeGdGJ (B4- (3efMfi GdJhRjY GdeYJOd (B5- (3GdefMfi GdGYJOGdj GdeYjGQj (B6-(3GdGSJOdGd GdEMUGFj GNJHGQ GdbQhV (B7(3JMdjd GdJHGjf (B8- (3GdGNJHGQGJ GdGMUGFjI GddGeYedjI Ch GdGMUGA GddeQeJQj JWHjbGJ GdEMUGA aj HMhK GdNOeI GdELJeGYjI (B.s
Keywords: (3GMUGAs; (3GdNOeGJ GdELJeGYjIs; (3JMdjd GMUGFjs